Role of sex hormone binding globulin as the early predictor for gestational diabetes mellitus - M. S., Sujatha; S., Madhana; P., Shylaja; S., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of this study was to find role of SHBG as an early predictor for gestational diabetes mellitus. Methods: A hospital based prospective/observational/diagnostic and explorative study. The necessary information was collected from the participants through the prepared set of questionnaires. Pregnant women between 11 to 14 weeks of gestation who visited JSS OPD for antenatal checkup satisfying inclusion and exclusion criteria giving informed and written consent for the study were examined clinically. 3ml of venous blood was drawn with aseptic precautions for the estimation of SHBG and adiponectin. OGTT with 75gms glucose first done at 11 to 14weeks and again at 24-28 weeks and 32-36 weeks were done to the same patient to find out whether the patient developed GDM or not. These mothers were followed periodically till delivery. The sensitivity and specificity of SHBG were assessed and compared in patients who developed GDM. Results: 100 cases were selected for the study. About 12 patients were diagnosed as gestational diabetes mellitus in present study by OGCT at 32 weeks to 36 weeks. In present study about 14 patients had low level of SHBG. Low level of SHBG is found to be statistically significant in predicting GDM in first trimester. Conclusions: The combination of SHBG can be used as predictor of GDM in first trimester.